The moral crisis in management - Petit, Thomas A. (New York : McGraw-Hill, 1967)
This study is future-oriented. Its underlying hypothesis is that there is now a moral crisis in management. A major objective of this study is to put some substance into the meaningful but vague idea of social responsibility of management.
Includes bibliographical references and index.
hza 04/09/2018
Loans
Keywords: Industries; Business ethics